Residual Capability of Alkali Binding by Hydrated Pozzolanic Cements in Long-Service Concrete Structures - Mario Berra; Teresa Mangialardi; Antonio Evangelista Paolini (Advances in Materials Science and Engineering)
An experimental procedure was developed and applied to cement pastes made with two different pozzolanic cements (CEM IV/B (P) and CEM IV/B (V)) in order to ascertain the existence of a residual capability of alkali binding by long-term hydrated pozzolanic cements and, at the same time, to evaluate the alkali retention capability and the concentration of OH− ions in the pore solution of such cementitious matrices. The developed procedure consisted of accelerated curing of cement paste specimens (150 days at 60°C and 100% RH), subsequent leaching tests at 60°C for 30 days by using deionized water or basic solutions (NaOH or KOH at different concentrations) as leaching media, and correlation of the leaching test results with a simple mass balance equation for sodium and potassium ions. The developed procedure was found to be appropriate for evaluating both the pore liquid alkalinity and the alkali retention capability by long-term hydrated pozzolanic cement pastes. A residual capability of alkali binding was also identified for both tested pozzolanic cements, thus indicating their potential ability to prevent (CEM IV/B (V)) or minimize (CEM IV/B (P)) the risk of deleterious expansion associated with alkali-aggregate reaction in long-service concrete structures, like concrete dams.